Pengaruh Ekstrak Buah Apel (Malus Sylvestris) Terhadap Perubahan Warna Gigi dalam Proses Bleaching (Pemutihan Gigi) Berdasarkan Perbedaan Konsentrasi - Setianingsih, Diana Riasari; Amalia, Rosa (Universitas Muhammadiyah Yogyakarta, 2008)
Bleaching is an oxidation process that involve free radicals through release electron. Bleaching material is hydrogen peroxide (H202). Apple contains ellagic acid, caffeic acid, klorogenic. Apple tissue has peroxidase that can be change into hydrogen peroxide with to help katalase. The aims of this research are to know the inï¬‚uence of apple extract on different concentration, so that can be used as alternative bleaching material.Subjects of this research consist of 20 teeth they are insisivus, caninus and premolar. This research used Rome Beauty Apple fruit extract with 10%, 3 0% and 50% concentration. The research are by doing degree measurement of color teeth changing with spectrophotometer on before and after inundate. Five teeth inundated on the apple extract with 10%, 3 0%, 50% concentration and the water as negative control for 96 hour: This research analysis used paired t-test and kruskal-wallis test.Results of paired t-test before and after of inundate on 10% concentration is p=0, 003 (p 0, 05) value, 30% concentration is p=0,006 (p 0, 05) value, and 50% concentration is p=0,099 (p 0,05) value. Results of Kruskal-Wallis test on the different value of inundate before and after is p=0,961 @ 0,05) value. Rate value on 10% concentration is 8, 30% concentration is 7,6 and 50% concentration is 8,6.Results of this research showed that there are different of color teeth changing to be whitener (lightner) between 10%, 30%, and 50% concentration but it is not fully signiï¬cant. Result of rate value concluded that whitening of teeth on material bleaching with 50% concentration more affective than 10% and 30% concentration.